Dynamics of red fluorescent dental plaque during experimental gingivitis—A cohort study - van der Veen, Monique H.; Volgenant, Catherine M.C.; Keijser, Bart; ten Cate, Jacob (Bob) M.; Crielaard, Wim (Journal of dentistry, 2016)
[Display omitted] The dynamics of red fluorescent plaque (RFP) in comparison to clinical plaque and bleeding scores were studied during an experimental gingivitis protocol in a cohort of healthy participants. Forty-one participants were monitored for RFP before (24h plaque), during 14 days plaque accumulation (days 2, 5, 9, 14) and after 7 days recovery (24h plaque). RFP was assessed on fluorescence photographs of the vestibular aspect of the anterior teeth (cuspid to cuspid) in the upper and lower jaw. Clinical plaque and bleeding were assessed at days −14, 0, 14 and 21. RFP of 24h plaque was reproducible (days −14, 0), then increased during 14 days plaque accumulation and returned to baseline after 7 days recovery. Groups of low, moderate and high RFP formers were statistically significantly different at all times even already at baseline. The individual RFP response during 14 days plaque accumulation correlated well with RFP of 24h plaque (days −14, 0). RFP correlated moderate to well with clinical plaque at days −14, 0, 14 and 21. From day 2 of the gingivitis challenge RFP correlated with bleeding at day 14. RFP provided an objective measure of oral hygiene status. Given the correlation with clinical parameters found, the amount of RFP after 24h plaque accumulation was indicatory for the inflammatory response during a prolonged period of no oral hygiene. This trial was registered at the public trial register ​of the Central Committee on Research Involving Human Subjects (CCMO) under number NL51111.029.14 This paper shows the association between RFP after 24h plaque accumulation and inflammatory response after a prolonged period of no oral hygiene. Red plaque fluorescence can be used to identify subjects at risk for developing gingival inflammation.